READERS' RESPONSES TO THE NOVELS OF HARRY POTTER - Rianita, Lilis (2007)
This study was triggered by the fact that reading habit among Indonesian people had not been developed well yet. Meanwhile, the teaching learning process of literature in schools, most of the time, is considered not to encourage the development of reading habit. Some teachers still tend to teach literature efferently instead of aesthetically. Their students are not given the opportunity and the courage to approach literature personally. In fact, by approaching literature personally, the students will probably learn more about literature and are more likely to become critical readers and learners. This research was attempted to investigate how elementary school students felt and thought when reading the novels of Harry Potter, i.e. how they responded to the novels when they were reading. This study was also aimed at seeking the similar and different responses to the novels made by the students and finding the background of the similarity and the difference. Factors influencing the students' reading habit were also investigated. This research was conducted qualitatively by involving nine students from the sixth grade of two schools in Bandung consisting of two boys and two girls from Assalaam; three boys and two girls from Bandung International School (B.I.S.). An open-ended questionnaire and a semi-structured interview were conducted to collect the data. Classification of the data was done to make them easy to interpret. The measure of reader stance on an efferent to aesthetic continuum proposed by Rosenblatt was employed to evaluate the students' responses. After the data had been analyzed, the following findings were gained: Assalaam and B.I.S students responded individually to the same stories based on their previous knowledge; the students responded similarly to the novels of Harry Potter, if they were impressed by universal values like love, loyalty, friendship, and courage. They responded differently to the same stories involving familiarity of the characters, events, places of the stories. Students' interests, social interaction, and their awareness of the importance of reading played important roles in students' reading habit.